Retrospective Analysis of Clinical Outcome of Intraoperative Epidural Steroid Injection Versus No Steroid Injection after Standard Lumbosacral Discectomy - Pandey, Suresh; Bidari, Suraj (Journal of College of Medical Sciences-Nepal, 2020)
Background: Despite operative decompression of neural structure with discectomy in the indicated cases of lumbosacral disc herniation, many patients continue to experience back pain and leg pain in the postoperative period. Use of intraoperative local epidural steroid injection has been in practice to reduce this complications but there are concern and controversies regarding its benefit and risk. So this study aims to analyze clinical outcome in terms of reduction in pain, hospital stay, postoperative use of analgesics and risk associated with the use of intraoperative epidural steroid locally and comparison to those who did not receive steroid. Methods: This was a retrospective analysis of total of 44 patients, 28 patients who received Epidural Steroid Injection (ESI) locally after lumbosacral standard discectomy and comparison of the outcome with results of 16 patients with standard lumbosacral discectomy who did not receive ESI. Outcome measurement was done between two groups in terms of postoperative pain VAS scale, use of analgesics, hospital stay and complications if any. Results: There were total of 44 cases (28 steroid group and 16 no steroid group) with mean age of 39.93 years, male 27 and female 17 who underwent standard discectomy and followed up for at least one year. Overall, preoperative mean VAS score for pain improved from 7.95 to 1.55 at 1 year after operation which was significant p<0.05. On comparison of 24 hour postoperative VAS score and hospital stay between the groups with steroid and no steroid, it was mean of 5.32 versus 6 and 4.43 days versus 5.25 days (p<0.05) respectively which was significant. All the patients in no steroid group needed both NSAID and opioids for the postoperative pain management whereas only 12 (42.8%) patient needed addition of opioids in steroid group. There was no difference in VAS score at 1week and 1 year. There was no complications in either of the group. Conclusions: Use of intraoperative ESI help to reduce early postoperative pain, hospital stay and use of opioids without adding further risk or complication.